Psychosocial Stress Before a Nap Increases Sleep Latency and Decreases Early Slow-Wave Activity - Ackermann, Sandra; Cordi, Maren; La Marca, Roberto; Seifritz, Erich; Rasch, Björn (Frontiers in Psychology, 2019)
Sleep disturbances are an important risk factor for stress-related diseases such as burnout or depression. In particular, slow-wave activity during sleep might be eminently relevant for optimal maintenance of mental health and cognitive functioning. In spite of the clinical importance and the pertinence of stress-related processes in everyday life, the physiological mechanisms of the association between stress, sleep and cognition are not well understood. In the present study, we carefully mapped the time course of the influence of a psychosocial stressor on sleep architecture and sleep-related oscillations during a midday nap. We induced stress using a psychosocial laboratory stressor, the Montreal Imaging Stress Task, vs. a neutral control task. Afterwards, participants were allowed to take a 90-minute nap (n=20) or stayed awake (n=19) and cortisol was measured via saliva samples. We hypothesized that stress would decrease sleep efficiency and slow-wave activity in a time-dependent manner, with impairing effects on cognitive functioning. Psychosocial stress resulted in increased cortisol levels, which were elevated throughout the study interval. In the nap group, psychosocial stress increased sleep latency, but had only minor effects on sleep architecture. Still, slow-wave activity in the first 30 minutes of sleep was significantly reduced, whereas alpha activity was enhanced. These effects vanished after approximately 30 minutes. No impairing effect on cognitive functioning occurred. Our results show that psychosocial stress before sleep has an impact on sleep latency and early slow-wave activity during sleep. In contrast to our hypothesis, the effects were rather small and short-lasting. Importantly, cognitive functioning was maintained. We conclude that the effects of psychosocial stress before a nap are possibly better compensated than previously believed.